Improvement of the mechanism for managing the investment activities of an industrial concern - Kaloshina, Marina Nikolaevna; Gabuev, Vladislav Vyacheslavovich (Nexo Revista Científica, 2021)
Competitive development of enterprises of the military industrial complex is determined by the implementation of promising investment projects. Amid a global reduction in military spending, military industrial enterprises need to improve their investment performance. This can be achieved due to a combination of factors, the strategic orientation of investment projects to the target guidelines for the organization’s activities being the most important of them. In this regard, the issue of creating an efficient system for managing the investment activities of an enterprise becomes urgent, because such system would contribute to the strategic focus of the ongoing investment projects and efficiently and quickly meet modern challenges. An economic mechanism for managing investment activities and special business processes, as well as procedures for the development and implementation of investment projects and programs by the life cycle stages described through algorithms have been developed for this purpose based on L. Hurwitz's theory of economic mechanisms. The strategic analysis of the activities of a Russian military industrial concern has allowed to formulate the concept of managing the entire concern and to determine the principles, methods, and tools of the business process. Improving the system for managing a set of projects as part of implementing the strategic objectives of the concern has required to improve, streamline, and unify the entire strategic management toolkit in order to increase the investment performance, with due consideration of the role models of responsibility centers and the current legislation. The automated information systems for strategic development and investment project management have been designed based on the outcomes of the research.